Windproof breathable composite fabric and application thereof

By pretreating the polyester fiber cloth and synthesizing modified polyurethane to form a stable padding finishing layer, the shortcomings of polyester fiber fabrics in terms of windproof, breathable, wear-resistant, anti-static and water-washing properties are solved, and higher fabric performance is achieved.

CN119571624AActive Publication Date: 2025-03-07BIEM L FDLKK GARMENT CO LTD

Patent Information

Application Number
CN202510139542.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

Existing polyester fiber fabrics need to be improved in terms of windproof, breathable, wear-resistant, anti-static and water-resistant properties.

Method used

The polyester fiber cloth is pretreated by a pretreatment solution to form an active fiber surface, and then the modified polyurethane is synthesized under the protection of an inert gas and mixed with tetrabutyl titanate and modified quaternary ammonium salt to form a stable padding finishing layer.

Benefits of technology

It significantly improves the windproof, moisture-permeable, anti-static, wear-resistant, lint-pilling and pilling performance of composite fabrics, and maintains good performance after washing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention discloses a windproof and breathable composite fabric and application thereof. The windproof and breathable composite fabric is used for solving the technical problem that in the prior art, the windproof and breathable performance, the wear-resistant and antistatic performance and the washing resistance of a polyester fiber fabric need to be further improved. The preparation method comprises the following steps: putting a gray fabric into a pretreatment solution for pretreatment to obtain a pretreated gray fabric, taking modified quaternary ammonium salt as a cross-linking agent, promoting cross-linking of a polyurethane prepolymer co-blocked by modified polysiloxane and polyethylene glycol, preparing epoxy group-terminated modified polyurethane, and carrying out heat treatment to obtain the pretreated gray fabric. The modified polyurethane and the tetrabutyl titanate are dispersed and mixed in the alkaline emulsion, and the prepared finishing liquid is used for padding and modifying the pretreated gray fabric, so that the windproof and moisture-permeable performance of the composite fabric is effectively improved, and the antistatic performance, wear resistance and pilling resistance of the composite fabric are also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabric processing, and in particular to a windproof and breathable composite fabric and application thereof. Background Art

[0002] Down jackets and cotton jackets are essential winter clothing. They are very popular because they are comfortable and light and can provide people with the best warmth. Polyester fiber fabrics are wrinkle-resistant, heat-resistant, chemical-resistant and easy to clean and maintain, and are widely used in clothing processing.

[0003] The polyester fiber fabric in the prior art is prone to pilling and static electricity when in use, and has poor permeability to moisture. In order to improve the relevant performance of the polyester fiber fabric, the fabric is usually modified by padding to form a padding modified layer on the fabric fiber; however, conventional padding modification is to form a physical coating on the fabric fiber by simple physical padding, and the padding modified layer is easily destroyed, resulting in a gradual decrease in its antistatic and anti-pilling properties. In addition, the modified film layer formed on the fabric layer by padding modification will also increase the coarseness of the fiber, reduce the size of the gaps between the fabric fibers, and further reduce the permeability of the polyester fiber fabric to moisture.

[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a windproof and breathable composite fabric and its application, which is used to solve the technical problem that the windproof and breathable performance, wear resistance, antistatic performance and washability of polyester fiber fabrics in the prior art need to be further improved.

[0006] The purpose of the present invention can be achieved by the following technical solution: A windproof and breathable composite fabric is obtained by processing the following steps:

[0007] S1, placing the blank in a pretreatment solution for pretreatment to obtain a pretreated blank;

[0008] S2, under the protection of inert gas, polyethylene glycol, hydroxyl-terminated polysiloxane, catalyst and butanone are mixed, the temperature of the reaction system is raised to 70-78 ° C, isophorone diisocyanate is added to the reaction system, and the reaction is kept warm for 90-120 minutes to obtain a polyurethane prepolymer, a modified quaternary ammonium salt is added to the reaction system, and the reaction is kept warm for 70-90 minutes, 2-(oxirane-2-yl) ethanol-1-ol is added to the reaction system, and the reaction is kept warm for 60-80 minutes, and post-processing is performed to obtain a modified polyurethane;

[0009] The synthetic reaction formula of modified polyurethane is:

[0010]

[0011]

[0012] Where:

[0013] ;

[0014] ;

[0015] .

[0016] The synthetic reaction mechanism of modified polyurethane is:

[0017] During the reaction, hydroxyl groups on polyethylene glycol and hydroxyl-terminated polysiloxane molecular chains are used as active reaction groups to condense with isocyanate groups on isophorone diisocyanate molecules. By controlling the molar ratio of isocyanate groups to hydroxyl groups, a polyurethane prepolymer having isocyanate-terminated polyethylene glycol and hydroxyl-terminated polysiloxane co-blocked segments is prepared. Then, the polyvalent hydroxyl groups on the modified quaternary ammonium salt molecules are used as active sites to promote the crosslinking of the polyurethane prepolymer molecular chains. 2-(2-oxirane-1-yl)ethane-1-ol is used as a capping agent, and the hydroxyl groups on the molecules of the 2-(2-oxirane-1-yl)ethane-1-ol are used as active groups to condense with isocyanate groups on the crosslinked polyurethane prepolymer molecules to form epoxy modification, thereby preparing the modified polyurethane.

[0018] S3, mixing the modified polyurethane, tetrabutyl titanate and the emulsion, stirring and emulsifying at high speed for 60-80 minutes to obtain a finishing liquid;

[0019] S4, immersing the modified grey fabric in a finishing solution, and adopting two-immersion and two-rolling finishing to obtain a composite fabric.

[0020] Further, in step S1, the pretreatment method is: adding the grey cloth to a pretreatment solution with a temperature of 60-70°C, ultrasonically dispersing for 30-50 minutes, and under ultrasonic dispersion, dripping 3-aminopropyltriethoxysilane solution into the pretreatment solution. After the dripping is completed, heat preservation treatment is performed for 60-80 minutes, and post-treatment is performed to obtain the pretreated grey cloth.

[0021] Furthermore, the grey cloth is a polyester fiber cloth, and the usage ratio of the grey cloth, the pretreatment solution and the 3-aminopropyltriethoxysilane solution is 5g:70mL:5g, the pretreatment solution is composed of 8-10g:100mL:3g:15-20mL of sodium hydroxide, purified water, sodium dodecyl sulfate and 30wt% hydrogen peroxide, and the 3-aminopropyltriethoxysilane solution is composed of 1g:3mL of 3-aminopropyltriethoxysilane and anhydrous ethanol. The post-treatment includes: after the treatment is completed, the grey cloth is removed from the solution, washed with purified water to neutrality and then dried to obtain the pretreated grey cloth.

[0022] Furthermore, in step S2, the amount ratio of the polyethylene glycol, the hydroxyl-terminated polysiloxane, the catalyst and the butanone is 10g:3g:0.1g:30mL, the molar ratio of the hydroxyl group to the isocyanate group is 1:1.1 during the preparation of the polyurethane prepolymer, the catalyst is dibutyltin dilaurate, the weight ratio of the polyethylene glycol, the modified quaternary ammonium salt and the 2-(ethylene oxide-2-yl)ethane-1-ol is 10:1.2-1.5:4, and the post-treatment includes: after the reaction is completed, the reaction system is kept warm at 70-78°C, and low boiling points are removed by distillation under reduced pressure to obtain a modified polyurethane.

[0023] Furthermore, in step S3, the modified polyurethane, tetrabutyl titanate and emulsion are used in a ratio of 10-20 g:0.8-1.2 g:40-60 mL, and the emulsion is composed of deionized water, hexadecyltrimethylammonium chloride, emulsifier AEO-4, Tween-80 and sodium carbonate in a ratio of 100 mL:2 g:1 g:1 g:15 g.

[0024] Further, in step S4, the two-immersion and two-rolling finishing operation includes: conveying the modified grey cloth to an immersion tank filled with a finishing liquid, dipping for 5-7 minutes, rolling out excess finishing liquid at a rolling rate of 30-40%, dipping the grey cloth in the finishing liquid again, dipping for 3-5 minutes, rolling out excess finishing liquid at a rolling rate of 75-85%, obtaining a rolled grey cloth, transferring the rolled grey cloth to a heat setting machine at a temperature of 80-90°C for pre-drying for 3-5 minutes, and then transferring it to a drying machine at a temperature of 140-150°C for drying to obtain a composite fabric crude product, and rubbing the composite fabric crude product with purified water and drying it to obtain a composite fabric.

[0025] Furthermore, the preparation method of hydroxyl-terminated polysiloxane is as follows: octamethylcyclotetrasiloxane, modified pyrimidine and xylene are mixed, a catalyst is added to the reaction system, the temperature of the reaction system is increased to 105-115°C, the reaction is kept warm for 3-4 hours, 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is added to the reaction system, the reaction is kept warm for 4-6 hours, and post-processed to obtain hydroxyl-terminated polysiloxane.

[0026] The synthetic reaction formula of hydroxyl-terminated polysiloxane is:

[0027]

[0028] Where:

[0029]

[0030] The synthetic reaction mechanism of hydroxyl-terminated polysiloxane is:

[0031] During the reaction, under the action of high temperature and catalyst, octamethylcyclotetrasiloxane is partially hydrolyzed to form a polysiloxane chain modified with silanol, and at the same time, the siloxane bonds on the modified pyrimidine molecules are hydrolyzed to form silanols, which are condensed to form silicon-oxygen-silicon bonds, thereby preparing a long polysiloxane chain modified with 2,6-dichloropyrimidine molecules. 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane molecules are used as end-capping agents, and the silanols formed after hydrolysis are condensed with the polysiloxane molecular chains to form hydroxyl modifications, thereby preparing hydroxyl-terminated polysiloxane.

[0032] Furthermore, the amount ratio of octamethylcyclotetrasiloxane, modified pyrimidine, xylene, catalyst and 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is 7g:2g:50mL:5mL:1g, the catalyst is a 10wt% formic acid aqueous solution, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, sodium hydroxide solution is added to the reaction system, the pH of the system is adjusted to 7, the liquid is allowed to stand and separate, the organic phase is washed with purified water 3 times, and xylene is evaporated under reduced pressure to obtain hydroxyl-terminated polysiloxane.

[0033] Furthermore, the preparation method of the modified pyrimidine is as follows: under the protection of an inert gas, 4-amino-2,6-dichloropyrimidine and tetrahydrofuran are mixed, the temperature of the reaction system is increased to 50-60° C., 3-isocyanatopropylmethyldiethoxysilane is added to the reaction system, the reaction is kept warm for 60-90 minutes, and post-processed to obtain the modified pyrimidine.

[0034] The synthetic reaction formula of modified pyrimidine is:

[0035]

[0036] The synthetic reaction mechanism of modified pyrimidine is:

[0037] During the reaction, the amino group on the 4-amino-2,6-dichloropyrimidine molecule undergoes a condensation reaction with the isocyanate group on the 3-isocyanatepropylmethyldiethoxysilane molecule, and the methyldiethoxysilane is modified on the 2,6-dichloropyrimidine molecule to prepare a modified pyrimidine;

[0038] The mass spectrometry data of modified pyrimidine are: m / z: 380.0838 (100.0%), 382.0809 (63.9%),

[0039] 381.0872(14.1%),384.0779(10.2%),383.0842(9.0%),381.0834(5.1%),382.0807(3.3%),383.0804(3.2%),384.0777(2.1%),381.0809(1.5%),385.0813(1.4%).

[0040] Furthermore, the usage ratio of 4-amino-2,6-dichloropyrimidine and 3-isocyanatopropylmethyldiethoxysilane is 1 mol:1 mol, and the usage ratio of 4-amino-2,6-dichloropyrimidine and tetrahydrofuran is 1 g:7 mL. The post-treatment includes: after the reaction is completed, distilling off tetrahydrofuran under reduced pressure to obtain modified pyrimidine.

[0041] Furthermore, the preparation method of the modified quaternary ammonium salt is: under the protection of inert gas, 1,4-dichlorobenzyl, triethanolamine and tetrahydrofuran are mixed, the temperature of the reaction system is increased to the reflux of the system, the reaction is kept warm for 6-8 hours, and post-processed to obtain the modified quaternary ammonium salt.

[0042] The synthetic reaction formula of modified quaternary ammonium salt is:

[0043]

[0044] The synthetic reaction mechanism of modified quaternary ammonium salt is:

[0045] During the reaction, 1,4-dichlorobenzyl as a halogenated hydrocarbon contains a chlorine atom on its molecule that can be attacked by a nucleophilic reagent. Ethanolamine as a nucleophilic reagent has a lone pair of electrons on its nitrogen atom that is nucleophilic. Tetrahydrofuran as a solvent can provide a polar environment that is conducive to the reaction. Under high temperature, benzyl chloride undergoes a nucleophilic substitution reaction with the nitrogen atom to form a quaternary ammonium salt, thereby preparing a modified quaternary ammonium salt.

[0046] The mass spectrometry data of the modified quaternary ammonium salt are: m / z: 472.2107 (100.0%), 474.2077 (63.9%),

[0047] 473.2140(21.6%),475.2111(13.8%),476.2048(10.2%),474.2174(2.2%),477.2081(2.2%),476.2145(1.4%),474.2149(1.2%).

[0048] Furthermore, the usage ratio of 1,4-dichlorobenzyl and triethanolamine is 1 mol:2 mol, the usage ratio of 1,4-dichlorobenzyl and tetrahydrofuran is 1 g:10 mL, and the post-treatment comprises: after the reaction is completed, distilling off tetrahydrofuran under reduced pressure to obtain a modified quaternary ammonium salt.

[0049] The present invention also provides an application of a windproof and breathable composite fabric, and applies the windproof and breathable composite fabric to clothing processing.

[0050] The present invention has the following beneficial effects:

[0051] 1. The windproof and breathable composite fabric of the present invention is prepared by soaking a polyester fiber cloth in a pretreatment solution. In the pretreatment solution, sodium hydroxide is used as an alkaline reagent to help activate the surface of the polyester fiber cloth, partially hydrolyze the ester bonds on the fiber surface, and increase the surface roughness and polarity. Hydrogen peroxide has oxidizing properties and can remove impurities and part of the oil stains on the surface of the fabric, further clean the surface of the fabric and induce weak oxidation on the fiber surface, thereby increasing reactive sites. The polyester fiber cloth is then modified by 3-aminopropyltriethoxysilane to introduce a large number of amino active sites into the polyester fiber cloth to prepare a pretreated grey cloth. After the grey cloth is finished with a finishing liquid, the epoxy groups on the molecules of the finishing liquid undergo ring-opening condensation with the amino groups to form a stable padding finishing layer on the polyester fiber fabric, thereby making it more resistant to water washing and improving the windproof and moisture permeability, antistatic and wear resistance and anti-pilling properties of the composite fabric.

[0052] 2. The windproof and breathable composite fabric of the present invention is prepared by introducing a polyurethane prepolymer co-blocked with hydroxyl-terminated polysiloxane modified with 2,6-dichloropyrimidine and polyethylene glycol on a modified polyurethane molecule. The polysiloxane segment has low surface energy and good flexibility and can form a continuous thin film on the fiber surface of the fabric. Polyethylene glycol is a hydrophilic polymer. The hydroxyl groups on its segment can form hydrogen bonds with water molecules to improve the moisture absorption and moisture permeability of the modified polyurethane. The 2,6-dichloropyrimidine modified on the hydroxyl-terminated polysiloxane molecular chain contains two chlorine atoms with high electronegativity and a pyrimidine ring in its molecular structure. The electronegativity of the chlorine atom attracts the surrounding electron cloud, thereby changing the charge distribution of the polyurethane prepolymer, resulting in stronger interaction forces between the polyurethane prepolymer segments, such as van der Waals forces and dipole-dipole interactions, further enhancing the interaction forces between molecules, making the film layer formed by the finishing agent impregnated on the polyester fiber fabric more compact, thereby improving the windproof and moisture permeability and the wear and anti-pilling properties of the fabric.

[0053] 3. The windproof and breathable composite fabric of the present invention is prepared by adding tetrabutyl titanate to a finishing liquid. In an alkaline emulsified environment, the tetrabutyl titanate is hydrolyzed to form cross-linked bonds with active groups such as imino groups and hydroxyl groups on modified polyurethane molecules, thereby forming titanium doping on the modified polyurethane, thereby enhancing the conductivity of the padding layer. The modified quaternary ammonium salt is used as a cross-linking agent. The quaternary ammonium salt molecules have cationic properties and can form a charge conduction layer on the fiber surface. When the fabric is rubbed or contacted, the generated static charge can be quickly dissipated through the charge conduction layer, thereby improving the antistatic performance of the composite fabric. The polyhydroxyl groups on the modified quaternary ammonium salt molecules are used as reactive active sites, thereby increasing the cross-linking points between the polyurethane prepolymer molecular chains, thereby making the film structure more stable. The windproof and moisture-permeable effect and the wear and anti-pilling performance are improved. The polysiloxane segment has a low friction coefficient and good lubricity, and can form a lubricating layer on the surface of the fiber fabric to reduce the friction and wear between the fibers, thereby improving the wear and anti-pilling performance of the fiber fabric. By adding sodium carbonate to the emulsion, an alkaline environment is provided for the emulsion. When the pretreated grey cloth is padded and modified, the alkaline environment can promote the reaction between the epoxy groups on the modified polyurethane molecules and the active sites on the pretreated grey cloth molecules, thereby improving the padded modification effect and water washing resistance of the modified grey cloth by the finishing liquid. At the same time, sodium carbonate, as a porogen, can be removed by water washing, thereby increasing the porosity of the padded film layer and further improving the overall performance of the composite fabric. DETAILED DESCRIPTION

[0054] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] The polyethylene glycol used in this application is PEG-1000.

[0056] Example 1

[0057] This embodiment provides a method for preparing a windproof and breathable composite fabric, comprising the following steps:

[0058] S1. Preparation of pre-treated grey fabric

[0059] Sodium hydroxide, purified water, sodium dodecyl sulfate and 30wt% hydrogen peroxide were mixed in a ratio of 8g:100mL:3g:15mL to obtain a pretreatment solution for later use;

[0060] 3-aminopropyltriethoxysilane and anhydrous ethanol were mixed evenly at a ratio of 1 g:3 mL to obtain a 3-aminopropyltriethoxysilane solution for later use;

[0061] Weigh: 7000 mL of the pretreatment solution is placed in a beaker, the temperature of the beaker is raised to 60°C, 500 g of polyester fiber cloth is added to the beaker, the polyester fiber cloth is completely immersed in the pretreatment solution, and ultrasonic dispersion is performed for 30 minutes. Under the ultrasonic dispersion state, 500 g of 3-aminopropyltriethoxysilane solution is added dropwise to the beaker. After the addition is completed, the heat treatment is carried out for 60 minutes, the grey cloth is removed from the beaker, washed with purified water until it is neutral, and then dried to obtain the pretreated grey cloth.

[0062] S2. Preparation of hydroxyl-terminated polysiloxane

[0063] Weigh: 16.4 g of 4-amino-2,6-dichloropyrimidine and 115 mL of tetrahydrofuran are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is raised to 50° C., 21.7 g of 3-isocyanatepropylmethyldiethoxysilane is added to the three-necked flask, and the reaction is kept warm for 60 minutes. The three-necked flask is kept warm at 50° C., and low-boiling substances are evaporated under reduced pressure to obtain modified pyrimidine;

[0064] Weigh: 70g of octamethylcyclotetrasiloxane, 20g of modified pyrimidine and 500mL of xylene are added to a three-necked flask and stirred, 50mL of 10wt% formic acid aqueous solution is added to the three-necked flask, the temperature of the three-necked flask is increased to 105°C, and the reaction is kept warm for 3h, 10g of 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is added to the three-necked flask, and the reaction is kept warm for 4h, the temperature of the three-necked flask is lowered to room temperature, 0.1mol / L sodium hydroxide solution is added to the three-necked flask, the pH of the system is adjusted to 7, and the liquid is separated by standing. The organic phase is washed 3 times with purified water, and then dried with anhydrous sodium sulfate for 2h. The organic phase is transferred to a rotary evaporator with a water bath temperature of 70°C, and low boiling substances are evaporated under reduced pressure to obtain a hydroxyl-terminated polysiloxane.

[0065] S3. Preparation of modified quaternary ammonium salt

[0066] Weigh: 17.5 g of 1,4-benzyl chloride, 29.8 g of triethanolamine and 175 mL of tetrahydrofuran, add into a three-necked flask and stir, raise the temperature of the three-necked flask to reflux, keep the temperature for 6 hours, lower the temperature of the three-necked flask to 50° C., remove low-boiling substances under reduced pressure, and obtain a modified quaternary ammonium salt.

[0067] S4. Preparation of modified polyurethane

[0068] Weigh: 50g of polyethylene glycol, 15g of hydroxyl-terminated polysiloxane, 0.5g of dibutyltin dilaurate and 150mL of butanone are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is raised to 70°C. Isophorone diisocyanate is weighed according to a molar ratio of hydroxyl group to isocyanate group of 1:1.1 and added to the three-necked flask. The reaction is kept warm for 90min. 6g of modified quaternary ammonium salt is added to the three-necked flask. The reaction is kept warm for 70min. 20g of 2-(oxirane-2-yl)ethane-1-ol is added to the three-necked flask. The reaction is kept warm for 60min. The three-necked flask is kept warm at 70°C. Low boiling substances are removed by distillation under reduced pressure to obtain a modified polyurethane.

[0069] S5. Preparation of finishing liquid

[0070] Deionized water, hexadecyltrimethylammonium chloride, emulsifier AEO-4, Tween-80 and sodium carbonate were uniformly mixed in a dosage ratio of 100mL:2g:1g:1g:15g to obtain an emulsion for later use;

[0071] The modified polyurethane, tetrabutyl titanate and emulsion were placed in a high-speed dispersant at a ratio of 10 g:0.8 g:40 mL, the stirring speed was set to 900 r / min, and the emulsification was carried out with high-speed stirring for 60 minutes to obtain a finishing liquid.

[0072] S6. Preparation of composite fabric

[0073] The modified grey fabric is transported to an impregnation tank filled with finishing liquid, and after impregnation for 5 minutes, the excess finishing liquid is squeezed out at a squeezing rate of 30% to obtain a once-impregnated fabric;

[0074] The once-impregnated cloth is immersed in the finishing liquid again for 3 minutes, and the excess finishing liquid is squeezed out at a squeezing rate of 75% to obtain a second-impregnated cloth;

[0075] The padding grey fabric is transferred to a heat setting machine at a temperature of 80°C for pre-drying for 3 minutes, and then transferred to a drying machine at a temperature of 140°C for drying to obtain a crude composite fabric;

[0076] The crude composite fabric is washed with purified water and then air-dried to obtain the composite fabric.

[0077] Example 2

[0078] This embodiment provides a method for preparing a windproof and breathable composite fabric, comprising the following steps:

[0079] S1. Preparation of pre-treated grey fabric

[0080] Sodium hydroxide, purified water, sodium dodecyl sulfate and 30wt% hydrogen peroxide were mixed in a ratio of 9g:100mL:3g:17mL to obtain a pretreatment solution for later use;

[0081] 3-aminopropyltriethoxysilane and anhydrous ethanol were mixed evenly at a ratio of 1 g:3 mL to obtain a 3-aminopropyltriethoxysilane solution for later use;

[0082] Weigh: 7000 mL of the pretreatment solution is placed in a beaker, the temperature of the beaker is raised to 65°C, 500 g of polyester fiber cloth is added to the beaker, the polyester fiber cloth is completely immersed in the pretreatment solution, and ultrasonic dispersion is performed for 40 minutes. Under the ultrasonic dispersion state, 500 g of 3-aminopropyltriethoxysilane solution is added dropwise to the beaker. After the addition is completed, the heat treatment is carried out for 70 minutes, the grey cloth is removed from the beaker, washed with purified water until it is neutral, and then dried to obtain the pretreated grey cloth.

[0083] S2. Preparation of hydroxyl-terminated polysiloxane

[0084] Weigh: 16.4 g of 4-amino-2,6-dichloropyrimidine and 115 mL of tetrahydrofuran are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is raised to 55° C., 21.7 g of 3-isocyanatepropylmethyldiethoxysilane is added to the three-necked flask, and the reaction is kept warm for 75 minutes. The three-necked flask is kept warm at 55° C., and low-boiling substances are evaporated under reduced pressure to obtain modified pyrimidine;

[0085] Weigh: 70g of octamethylcyclotetrasiloxane, 20g of modified pyrimidine and 500mL of xylene are added to a three-necked flask and stirred, 50mL of 10wt% formic acid aqueous solution is added to the three-necked flask, the temperature of the three-necked flask is increased to 110°C, and the reaction is kept warm for 3.5h, 10g of 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is added to the three-necked flask, and the reaction is kept warm for 5h, the temperature of the three-necked flask is lowered to room temperature, 0.15mol / L sodium hydroxide solution is added to the three-necked flask, the pH of the system is adjusted to 7, and the liquid is separated by standing. The organic phase is washed 3 times with purified water, and then dried with anhydrous sodium sulfate for 2.5h. The organic phase is transferred to a rotary evaporator with a water bath temperature of 75°C, and low boiling substances are evaporated under reduced pressure to obtain a hydroxyl-terminated polysiloxane.

[0086] S3. Preparation of modified quaternary ammonium salt

[0087] Weigh: 17.5 g of 1,4-dichlorobenzyl, 29.8 g of triethanolamine and 175 mL of tetrahydrofuran, add into a three-necked flask and stir, raise the temperature of the three-necked flask to reflux the system, keep the temperature for 7 hours, lower the temperature of the three-necked flask to 53° C., remove low-boiling substances under reduced pressure, and obtain a modified quaternary ammonium salt.

[0088] S4. Preparation of modified polyurethane

[0089] Weigh: 50g of polyethylene glycol, 15g of hydroxyl-terminated polysiloxane, 0.5g of dibutyltin dilaurate and 150mL of butanone are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is raised to 74°C. Isophorone diisocyanate is weighed according to a molar ratio of hydroxyl group to isocyanate group of 1:1.1 and added to the three-necked flask. The reaction is kept warm for 105min. 7.0g of modified quaternary ammonium salt is added to the three-necked flask, and the reaction is kept warm for 80min. 20g of 2-(oxirane-2-yl)ethane-1-ol is added to the three-necked flask, and the reaction is kept warm for 70min. The three-necked flask is kept warm at 704°C, and low boiling substances are removed under reduced pressure to obtain a modified polyurethane.

[0090] S5. Preparation of finishing liquid

[0091] Deionized water, hexadecyltrimethylammonium chloride, emulsifier AEO-4, Tween-80 and sodium carbonate were uniformly mixed in a dosage ratio of 100mL:2g:1g:1g:15g to obtain an emulsion for later use;

[0092] The modified polyurethane, tetrabutyl titanate and emulsion were placed in a high-speed dispersant at a ratio of 15 g:1.0 g:50 mL, the stirring speed was set to 1050 r / min, and the emulsification was carried out with high-speed stirring for 70 minutes to obtain a finishing liquid.

[0093] S6. Preparation of composite fabric

[0094] The modified grey cloth is transported to an impregnation tank filled with finishing liquid, and after impregnation for 6 minutes, the excess finishing liquid is squeezed out at a squeezing rate of 35% to obtain a once-impregnated cloth;

[0095] The once-impregnated cloth is immersed in the finishing liquid again for 4 minutes, and the excess finishing liquid is squeezed out at a squeezing rate of 80% to obtain a second-impregnated cloth;

[0096] The padding grey fabric was transferred to a heat setting machine at a temperature of 85°C for pre-drying for 4 minutes, and then transferred to a drying machine at a temperature of 145°C for drying to obtain a crude composite fabric;

[0097] The crude composite fabric is washed with purified water and then air-dried to obtain the composite fabric.

[0098] Example 3

[0099] This embodiment provides a method for preparing a windproof and breathable composite fabric, comprising the following steps:

[0100] S1. Preparation of pre-treated grey fabric

[0101] Sodium hydroxide, purified water, sodium dodecyl sulfate and 30wt% hydrogen peroxide were mixed in a ratio of 10g:100mL:3g:20mL to obtain a pretreatment solution for later use;

[0102] 3-aminopropyltriethoxysilane and anhydrous ethanol were mixed evenly at a ratio of 1 g:3 mL to obtain a 3-aminopropyltriethoxysilane solution for later use;

[0103] Weigh: 7000 mL of the pretreatment solution is placed in a beaker, the temperature of the beaker is raised to 70°C, 500 g of polyester fiber cloth is added to the beaker, the polyester fiber cloth is completely immersed in the pretreatment solution, and ultrasonic dispersion is performed for 50 minutes. Under the ultrasonic dispersion state, 500 g of 3-aminopropyltriethoxysilane solution is added dropwise to the beaker. After the addition is completed, the heat treatment is carried out for 80 minutes, the grey cloth is removed from the beaker, washed with purified water until it is neutral, and then dried to obtain the pretreated grey cloth.

[0104] S2. Preparation of hydroxyl-terminated polysiloxane

[0105] Weigh: 16.4 g of 4-amino-2,6-dichloropyrimidine and 115 mL of tetrahydrofuran are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is raised to 60° C., 21.7 g of 3-isocyanatepropylmethyldiethoxysilane is added to the three-necked flask, and the reaction is kept warm for 90 minutes. The three-necked flask is kept warm at 60° C., and low-boiling substances are evaporated under reduced pressure to obtain modified pyrimidine;

[0106] Weigh: 70g of octamethylcyclotetrasiloxane, 20g of modified pyrimidine and 500mL of xylene are added to a three-necked flask and stirred, 50mL of 10wt% formic acid aqueous solution is added to the three-necked flask, the temperature of the three-necked flask is increased to 115°C, and the reaction is kept warm for 4h, 10g of 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is added to the three-necked flask, and the reaction is kept warm for 6h, the temperature of the three-necked flask is lowered to room temperature, 0.2mol / L sodium hydroxide solution is added to the three-necked flask, the pH of the system is adjusted to 7, and the liquid is separated by standing. The organic phase is washed 3 times with purified water, and then dried with anhydrous sodium sulfate for 3h. The organic phase is transferred to a rotary evaporator with a water bath temperature of 80°C, and low boiling substances are evaporated under reduced pressure to obtain a hydroxyl-terminated polysiloxane.

[0107] S3. Preparation of modified quaternary ammonium salt

[0108] Weigh: 17.5 g of 1,4-benzyl chloride, 29.8 g of triethanolamine and 175 mL of tetrahydrofuran, add into a three-necked flask and stir, raise the temperature of the three-necked flask to reflux the system, keep the temperature for 8 hours, lower the temperature of the three-necked flask to 55° C., remove low boiling substances under reduced pressure, and obtain a modified quaternary ammonium salt.

[0109] S4. Preparation of modified polyurethane

[0110] Weigh: 50g of polyethylene glycol, 15g of hydroxyl-terminated polysiloxane, 0.5g of dibutyltin dilaurate and 150mL of butanone are added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask is raised to 78°C. Isophorone diisocyanate is weighed according to the molar ratio of hydroxyl group to isocyanate group of 1:1.1 and added to the three-necked flask. The reaction is kept warm for 120min. 7.5g of modified quaternary ammonium salt is added to the three-necked flask, and the reaction is kept warm for 90min. 20g of 2-(oxirane-2-yl)ethane-1-ol is added to the three-necked flask, and the reaction is kept warm for 80min. The three-necked flask is kept warm at 78°C, and low boiling substances are removed under reduced pressure to obtain a modified polyurethane.

[0111] S5. Preparation of finishing liquid

[0112] Deionized water, hexadecyltrimethylammonium chloride, emulsifier AEO-4, Tween-80 and sodium carbonate were uniformly mixed in a dosage ratio of 100mL:2g:1g:1g:15g to obtain an emulsion for later use;

[0113] The modified polyurethane, tetrabutyl titanate and emulsion were placed in a high-speed dispersant at a ratio of 20 g:1.2 g:60 mL, the stirring speed was set to 1200 r / min, and the emulsification was carried out with high-speed stirring for 80 minutes to obtain a finishing liquid.

[0114] S6. Preparation of composite fabric

[0115] The modified grey fabric is transported to an impregnation tank filled with finishing liquid, and after impregnation for 7 minutes, the excess finishing liquid is squeezed out at a squeezing rate of 40% to obtain a once-impregnated fabric;

[0116] The once-impregnated cloth is immersed in the finishing liquid again for 5 minutes, and the excess finishing liquid is squeezed out at a squeezing rate of 85% to obtain a second-impregnated cloth;

[0117] The padding grey fabric was transferred to a heat setting machine at a temperature of 90°C for pre-drying for 5 minutes, and then transferred to a drying machine at a temperature of 150°C for drying to obtain a crude composite fabric;

[0118] The crude composite fabric is washed with purified water and then air-dried to obtain the composite fabric.

[0119] Comparative Example 1

[0120] The difference between this comparative example and Example 3 is that in step S1, when preparing the pretreated grey cloth, no 3-aminopropyltriethoxysilane solution is added.

[0121] Comparative Example 2

[0122] The difference between this comparative example and Example 3 is that in step S2, when preparing the hydroxyl-terminated polysiloxane, no modified pyrimidine is added.

[0123] Comparative Example 3

[0124] The difference between this comparative example and Example 3 is that step S3 is eliminated, and the modified quaternary ammonium salt in step S4 is replaced by an equimolar amount of triethanolamine in step S3.

[0125] Comparative Example 4

[0126] The difference between this comparative example and Example 3 is that in step S5, no sodium carbonate is added to the emulsion.

[0127] Performance Testing:

[0128] The air permeability and moisture permeability of the composite fabric samples prepared in Examples 1-3 and Comparative Examples 1-4 were measured with reference to Standard FZ / T01149-2019 “Evaluation of windproof and moisture permeability of textiles”;

[0129] The antistatic properties of the composite fabric samples prepared in Examples 1-3 and Comparative Examples 1-4 were determined with reference to the standard GB / T12703.1-2021 "Test method for electrostatic properties of textiles - Part 1: Corona charging method";

[0130] The number of friction pilling of the composite fabric samples prepared in Examples 1-3 and Comparative Examples 1-4 under a chuck pressure of 590 cN was measured with reference to the standard GB / T4802.1-2008 "Determination of pilling properties of textile fabrics Part 1: Circular locus method";

[0131] The composite fabric samples prepared in Examples 1-3 and Comparative Examples 1-4 were washed, and various properties of the samples after washing 80 times were measured according to the above standards. The specific test results are shown in Table 1 below.

[0132] Table 1-Performance test data of the sample

[0133]

[0134] Data Analysis:

[0135] Comparing and analyzing the data in Table 1 above, the air permeability of the composite fabric prepared by the present invention is reduced to 8.4 mm / s, and the moisture permeability reaches 5930 g / (m 2·24h), the number of friction pilling reached 180 times, and, after being washed 80 times, the air permeability retention rate reached 95.45%, the moisture permeability retention rate reached 98.02%, and the number of friction pilling reached 98.87%. It had good antistatic performance before and after washing, and various performance parameters were better than those of the comparative example, indicating that the present invention uses modified quaternary ammonium salt as a cross-linking agent to promote the cross-linking of the polyurethane prepolymer co-blocked with modified polysiloxane and polyethylene glycol, prepares the epoxy-terminated modified polyurethane, and disperses and mixes the modified polyurethane with tetrabutyl titanate in an alkaline emulsion to perform padding modification on the pretreated grey cloth, which not only effectively improves the windproof and moisture permeability of the composite fabric, but also improves its antistatic performance and wear resistance and anti-pilling performance.

[0136] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A windproof and breathable composite fabric, characterized in that: It is processed by the following steps: S1, placing the blank in a pretreatment solution for pretreatment to obtain a pretreated blank; S2, under the protection of inert gas, polyethylene glycol, hydroxyl-terminated polysiloxane, catalyst and butanone are mixed, the temperature of the reaction system is raised to 70-78 ° C, isophorone diisocyanate is added to the reaction system, and the reaction is kept warm for 90-120 minutes to obtain a polyurethane prepolymer, a modified quaternary ammonium salt is added to the reaction system, and the reaction is kept warm for 70-90 minutes, 2-(oxirane-2-yl) ethanol-1-ol is added to the reaction system, and the reaction is kept warm for 60-80 minutes, and post-processing is performed to obtain a modified polyurethane; S3, mixing the modified polyurethane, tetrabutyl titanate and the emulsion, stirring and emulsifying at high speed for 60-80 minutes to obtain a finishing liquid; S4, immersing the modified grey fabric in a finishing solution, and adopting two-immersion and two-rolling finishing to obtain a composite fabric.

2. A windproof and breathable composite fabric according to claim 1, characterized in that: In step S1, the pretreatment method is: adding the grey cloth to a pretreatment solution with a temperature of 60-70°C, ultrasonically dispersing for 30-50 minutes, and dripping 3-aminopropyltriethoxysilane solution into the pretreatment solution under ultrasonic dispersion. After the dripping is completed, heat preservation treatment is performed for 60-80 minutes, and post-treatment is performed to obtain the pretreated grey cloth.

3. A windproof and breathable composite fabric according to claim 2, characterized in that: The grey cloth is a polyester fiber cloth, and the usage ratio of the grey cloth, the pretreatment solution and the 3-aminopropyltriethoxysilane solution is 5g:70mL:5g, the pretreatment solution is composed of 8-10g:100mL:3g:15-20mL of sodium hydroxide, purified water, sodium dodecyl sulfate and 30wt% hydrogen peroxide, and the 3-aminopropyltriethoxysilane solution is composed of 3-aminopropyltriethoxysilane and anhydrous ethanol at 1g:3mL.

4. The windproof and breathable composite fabric according to claim 1, characterized in that: In step S2, the amount ratio of the polyethylene glycol, hydroxyl-terminated polysiloxane, catalyst and butanone is 10g:3g:0.1g:30mL, in the preparation process of the polyurethane prepolymer, the molar ratio of the hydroxyl group to the isocyanate group is 1:1.1, the catalyst is dibutyltin dilaurate, and the weight ratio of the polyethylene glycol, modified quaternary ammonium salt and 2-(ethylene oxide-2-yl)ethane-1-ol is 10:1.2-1.5:4; in step S3, the amount ratio of the modified polyurethane, tetrabutyl titanate and emulsion is 10-20g:0.8-1.2g:40-60mL, and the emulsion is composed of deionized water, hexadecyltrimethylammonium chloride, emulsifier AEO-4, Tween-80 and sodium carbonate in an amount ratio of 100mL:2g:1g:1g:15g.

5. The windproof and breathable composite fabric according to claim 1, characterized in that: The preparation method of hydroxyl-terminated polysiloxane is as follows: octamethylcyclotetrasiloxane, modified pyrimidine and xylene are mixed, a catalyst is added to the reaction system, the temperature of the reaction system is increased to 105-115°C, the reaction is kept warm for 3-4 hours, 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is added to the reaction system, the reaction is kept warm for 4-6 hours, and post-processing is performed to obtain hydroxyl-terminated polysiloxane.

6. The windproof and breathable composite fabric according to claim 5, characterized in that: The usage ratio of the octamethylcyclotetrasiloxane, modified pyrimidine, xylene, catalyst and 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane is 7g:2g:50mL:5mL:1g, and the catalyst is a 10wt% formic acid aqueous solution.

7. The windproof and breathable composite fabric according to claim 5, characterized in that: The preparation method of the modified pyrimidine is as follows: under the protection of inert gas, 4-amino-2,6-dichloropyrimidine and tetrahydrofuran are mixed, the temperature of the reaction system is increased to 50-60°C, 3-isocyanatopropylmethyldiethoxysilane is added to the reaction system, the reaction is kept warm for 60-90 minutes, and post-processed to obtain the modified pyrimidine.

8. The windproof and breathable composite fabric according to claim 7, characterized in that: The usage ratio of the 4-amino-2,6-dichloropyrimidine to 3-isocyanatopropylmethyldiethoxysilane is 1 mol:1 mol, and the usage ratio of the 4-amino-2,6-dichloropyrimidine to tetrahydrofuran is 1 g:7 mL.

9. The windproof and breathable composite fabric according to claim 1, characterized in that: The preparation method of the modified quaternary ammonium salt is as follows: under the protection of inert gas, 1,4-dichlorobenzyl, triethanolamine and tetrahydrofuran are mixed, the temperature of the reaction system is increased to the system reflux, the reaction is kept warm for 6-8 hours, and post-processed to obtain the modified quaternary ammonium salt, wherein the usage ratio of 1,4-dichlorobenzyl and triethanolamine is 1 mol:2 mol.

10. An application of a windproof and breathable composite fabric, characterized in that: The windproof and breathable composite fabric described in any one of claims 1 to 9 is applied to clothing processing.

Citation Information

Patent Citations

  • Preparation method of nanometer in situ composite reaction type organic silicone modified cationic water-based polyurethane and product thereof

    CN102199274A

  • Windproof breathable composite fabric

    CN110528288A

  • Setting agent as well as preparation method and application thereof

    CN116655885A

  • Environment-friendly breathable polyester silk fabric and preparation process thereof

    CN119392504A

  • WATERPROOF, MOISTURE-PERMEABLE FUNCTIONAL FABRIC

    DE102022116534A1

Cited By

  • High-dispersion anti-migration TPU color master batch and preparation method thereof

    CN120329712A

  • Windproof composite gradient wetting one-way moisture guiding sportswear fabric and preparation method thereof

    CN121019077A